ISOLASI DAN IDENTIFIKASI SENYAWA KIMIA SERTA UJI AKTIVITAS ANTICANDIDAISIS SERBUK BATANG SIRIH DUDUK (Piper sarmentosum Roxb. Ex Hunter) - Suwandri Suwandri; Hartiwi Diastuti; Purwati Purwati (Universitas Jenderal Soedirman, 2007)
Sirih duduk or Piper sarmentosum Roxb. ex Hunter have been long used the people in Indonesia for traditional medicine to cure various diseases. One of them was used to treat fungoid diseases. This research was aimed to examine the anticandidaisis activity from extract of P. sarmentosum bark, isolate and identify anticandidaisis compounds from P. sarmentosum bark. The isolation of bioactive compounds of P. sarmentosum bark was performed by extraction the powder of P. sarmentosum bark using methanol. The methanol extract was then fractionated using n-hexane, chloroform and ethylasetat. The fractions respectively was examined their activity against C. albican. The active extract was then fractionated performed by coloumn chromatography and was then separated performed by thin layer chromatography. Identification of bioactive compound was carry out using gas chromatography-mass spectrometry (GC-MS). The results show that chloroform, ethylasetat and methanol extracts of P. sarmentosum have more activities against C. albicans than miconazol. Bioactive compound from extract of P. sarmentosum bark was bis(2-ethylhexyl)phtalat.